Determinants of Internal Control System Quality at Vocational High School - Amanda Bella Paramitha; Nurhasan Hamidi (Program Studi Manajemen Pendidikan, 2024)
This study aims to examine (1) the influence between teacher citizenship behavior and internal control system quality at vocational high schools; (2) the influence between internal quality audits and internal control system quality at vocational high school;(3) the influence between local wisdom value-based management and internal control system quality at vocational high school. The method of the study was based on descriptive quantitative. The sampel of this study were 57 of A-accredited public and private vocational high schools includes: Surakarta, Klaten, Karanganyar, Sragen, Sukoharjo and Boyolali. The data was collected by questionnaire. The Confirmatory Factor Analysis (CFA) approach was used to examine this study model, which was aided by SmartPLS Version 3.0 software. The results of the study show that (1) there is a significantly affect between teacher citizenship behavior and internal control system quality at vocational high school. This is evidenced by p-value of 0.000 < 0.05; (2) there is a significantly affect between internal quality audit and internal control system quality at vocational high schools. This is evidenced by p-value of 0.028 < 0.05; (3) there is a significantly affect between local wisdom value-based management and internal control system quality at vocational high school. This is evidenced by p-value of 0.000 < 0.05.